Qarābādhīn (Pharmacopoeia) in Greeco-Arabian era : A Historical and Regulatory Perspective - Ali, Mohd Akhtar; Hamiduddin, - (International Journal of Human and Health Sciences (IJHHS), 2021)
Qarābādhīn can be termed as pharmacopoeia, contains compiled form of compound formulations or recipes. Importance of Qarābādhīn gradually increased and acquired an imperative status. The history of Qarābādhīn starts from Chiron, Aesculapius, Hippocrates, Dioscorides and Galen in Greco-Roman era. Many of early and medieval Islamic and Arab physicians play vital role and immense original contribution in this discipline and authored important and essential Qarābādhīn with systemic and scientific approaches. Although some of them could not reach the present day, many of the manuscripts can be found in various libraries across the world. Since the Arab Caliphates appreciated and patronized the fields of medicine acquired from Greeks and worked for its development, this period also known as “Greco-Arabic era”. In this work the evaluation of Qarābādhīn (particularly written in Arabic or Greek language) was done in historical and regulatory perspective particularly in Greek era and later on in Medieval Islamic era. The findings of the review indicate the importance and regulatory status of Qarābādhīn and provide information about it. It can be helpful to explore Qarābādhīn and related publications of Greek and Medieval Islamic Arabic period, which gives foundations for the present-day pharmacopeias. Since these documents also take into account ethical considerations, its utility in the fields of medicine and medical ethics should be investigated. International Journal of Human and Health Sciences Vol. 05 No. 04 October’21 Page: 388-404